Solid Phase Extraction and Determination of Nickel Ions in Samples of Steel and Hydrogenated Oils Using Modified Cellulose - Chahar, M.; Khaturia, S.; Soni, K.P.; Bhojak, N. (Asian Journal of Chemistry, 2010)
2-Pyridyliminosalicyl cellulose has been used for the adsorption and estimation of nickel by both column and batch techniques. The distribution coefficient has been determined for nickel ions. Methods have been developed to estimate nickel in steel and hydrogenated oil samples.